2015
DOI: 10.1007/s12017-015-8382-6
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Profiling in the Brain of CLN1 Disease Model Reveals Affected Functional Modules

Abstract: Neuronal ceroid lipofuscinoses (NCL) are the most commonly inherited progressive encephalopathies of childhood. Pathologically, they are characterized by endolysosomal storage with different ultrastructural features and biochemical compositions. The molecular mechanisms causing progressive neurodegeneration and common molecular pathways linking expression of different NCL genes are largely unknown. We analyzed proteome alterations in the brains of a mouse model of human infantile CLN1 disease-palmitoyl-protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 122 publications
(167 reference statements)
3
46
0
Order By: Relevance
“…Dysregulated thalamic proteins to a variety of signalling pathways, including Huntington disease signalling, have been detected in the PPT1-deficient thalamus and supported by RNA sequencing data in the fibroblasts of patients with CLN1. 25 In conclusion, the cohort of patients described herein raises to 40 the number of reported patients affected with CLN5 disease, late infantile. Analysis of data obtained by this study has provided some new evidence and confirmed previous experience.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Dysregulated thalamic proteins to a variety of signalling pathways, including Huntington disease signalling, have been detected in the PPT1-deficient thalamus and supported by RNA sequencing data in the fibroblasts of patients with CLN1. 25 In conclusion, the cohort of patients described herein raises to 40 the number of reported patients affected with CLN5 disease, late infantile. Analysis of data obtained by this study has provided some new evidence and confirmed previous experience.…”
Section: Discussionmentioning
confidence: 79%
“…A systems biology approach might identify which pathways are dysregulated in the NCLs, and possibly explain the gradient of neural system involvement. Dysregulated thalamic proteins to a variety of signalling pathways, including Huntington disease signalling, have been detected in the PPT1‐deficient thalamus and supported by RNA sequencing data in the fibroblasts of patients with CLN1 …”
Section: Discussionmentioning
confidence: 99%
“…An alteration of the axon guidance processes has been so far supposed only for other three LSDs: In the drosophila model for Batten disease [30], in the brain of the MPS VII mouse [8] and in the brain of a mouse model for CLN1 disease [31]. …”
Section: Discussionmentioning
confidence: 99%
“…Proteins linked to Rho GTPase family are also relevant for axon guidance, and aberration of the neuronal outgrowth was observed at the pre-symptomatic stage in the brain of CLN1 mouse model [31]. Cytoskeletal alterations have been observed also in Krabbe, Pompe and Niemann–Pick type C diseases [40,41,42] and in other adult-onset disorders of the nervous system, such as Charcot–Marie–Tooth, Alzheimer’s disease, Parkinson’s disease [26].…”
Section: Discussionmentioning
confidence: 99%
“…In fibroblasts from patients with infantile CLN1 disease, fragmented mitochondrial reticulum was observed, and reduced activities of ATP synthase and respiratory chain complexes II and IV were reported (32, 33). A recent proteomic analysis of the thalamus and cerebral cortex of symptomatic Ppt1 −/− mice found changes in the expression level of mitochondrial proteins, including decreased levels of cytochrome c oxidase subunit 7C and 2 proteins in the Fo complex of ATP synthase (34). Notably, the F1 complex of ATP synthase interacts with PPT1 (35).…”
Section: Discussionmentioning
confidence: 99%